The Effectiveness of Padang Mayor Regulation No. 25 of 2023 on the 112 Emergency Call Service in Responding to Emergencies in Padang City - Lania Chairanisa; Lince Magriasti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research was prompted by the implementation of Padang Mayor Regulation Number 25 of 2023 concerning the 112 Emergency Call Service, which aims to provide rapid, integrated, and easily accessible emergency services. However, implementation faces challenges such as low public awareness, suboptimal outreach, and a high volume of prank and ghost calls. This study aims to analyze the effectiveness of Padang Mayor Regulation Number 25 of 2023 regarding the 112 Emergency Call Service in handling emergencies in Padang City. A qualitative approach with a descriptive method was employed. Informants were selected using purposive sampling and included representatives from the Padang City Communication and Informatics Agency, PCC 112 operators, the Regional Disaster Management Agency (BPBD), the Fire Department, the Public Order Enforcers (Satpol PP), and the general public. Data collection involved observation, interviews, and documentation review, while data analysis utilized data reduction, data presentation, and conclusion drawing. The results indicate that the PCC 112 service has performed effectively based on indicators of achievement, integration, and adaptation. The service facilitates public access to emergency assistance through a single call number and enhances inter-agency coordination. However, service effectiveness remains suboptimal due to challenges such as low public awareness, uneven outreach, and the high frequency of prank and ghost calls, which impact operator performance. Therefore, increased public outreach, human resource capacity building, and service system improvements are necessary to optimize the 112 emergency call service.